Music, power, and politics - Randall, Annie Janeiro (Routledge, 2005)
Essays by scholars from around the world explore the means by which music's long-acknowledged potential to persuade, seduce, indoctrinate, rouse, incite, or even silence listeners has been used to advance agendas of power and protest.